Fabricating M/Al2O3/cordierite (M = Cr, Mn, Fe, Co, Ni and Cu) monolithic catalysts for ethyl acetate efficient oxidation: Unveiling the role of water vapor and reaction mechanism. (1st November 2021) - Ma, Mudi; Yang, Rui; Jiang, Zeyu; Chen, Changwei; Liu, Qiyuan; Albilali, Reem; He, Chi
Graphical abstract: Highlights: A series of transition metal cordierite-based monolithic catalysts were prepared. Mn/Al2 O3 /COR shows excellent ethyl acetate (EA) oxidation activity and water resistance. Surface oxygen species ( O β ) play vital roles in EA activation and intermediate generation. Low content water vapor (≤1 vol%) promotes EA activation and ethanol formation. Water vapor leads to the decline of O β and formation of large-size hard coke. Abstract: The reduction and control of VOCs from anthropogenic sources becomes a research hotspot due to their tremendous environment hazards. Fabricating efficient and applicable noble-metal-free monolithic catalysts is still a great challenge for industrial VOC economical removal. In this work, cordierite-based honeycomb monolithic catalysts (M/Al2 O3 /COR; M = Cr, Mn, Fe, Co, Ni and Cu) were synthesized by a versatile and scalable wash-coating method and adopted for ethyl acetate (EA) catalytic oxidation. Mn/Al2 O3 /COR possesses remarkable activity with 90% of ethyl acetate (EA) oxidized at 236 °C owing to abundant surface active oxygen species. Moreover, excellent stability and water resistance of Mn/Al2 O3 /COR were observed during long-term successive reaction. In situ DRIFTS results reveal that the decomposition of EA to ethanol is the main pathway under humid conditions, and the presence of low content water vapor (≤1 vol%) promotes EA conversion ascribed to the presence of abundant OH derived from H2 O dissociation; however, further increasing of water concentration inhibits EA conversion. The adsorption of OH over oxygen vacancies inhibits the generation of surface oxygen species and blocks further oxidation of intermediates to form acetate, leading to the reduction of CO2 yield and formation of coke aggregates. This work will provide instructive and feasible references for designing of VOC oxidation catalysts under practical reaction conditions.